Modeling Equilibrium of microRNA Expression - Chan, Lawrence W. (Frontiers in Genetics, 2011)
MicroRNAs are a class of non-coding RNAs and the dysregulated expression of these short RNA molecules was frequently observed in cancer cells. The steady state level of microRNA concentration may differentiate the biological function of the cells between normal and impaired. To understand the steady state or equilibrium of microRNAs, their interactions with transcription factors and target genes need to be explored and visualized through prediction and network analysis algorithms. This article discusses the application of mathematical model for simulating the dynamics of network feedback loop so as to decipher the mechanism of microRNA regulation.